Enterprises and Institutions in Bosnia and Herzegovina and Web 2.0 Technologies (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Web 2.0 offers great tools for building better customer relationships, improving employees’ productivity, and cutting costs. Results of different international research showed that many companies recognize the benefits of Web 2.0 technologies and use it in everyday business. But what is the situation in Bosnia and Herzegovina?!In order to investigate that, empirical research was conducted. The objective was to investigate whether Web 2.0 technologies are applied in companies and institutions in Bosnia and Herzegovina, and which ones. The paper presents the results of research among 107 companies and institutions in Bosnia and Herzegovina on the current application of Web 2.0 technologies in business. The results show that 49.5% of respondents use Web 2.0, mostly Internet telephony and Business social networks, while 31.7% of respondents who do not use it, plan to start using some of it in the next year. Although the results show that Web 2.0 technologies are not totally unknown in Bosnia and Herzegovina (at least some of it), there is much room for improvement. Further research should investigate what hinders the implementation of Web 2.0 technologies and particularly address the characteristics of the companies and institutions that may significantly affect their acceptance and implementation.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.